2011
DOI: 10.3945/ajcn.110.006668
|View full text |Cite
|
Sign up to set email alerts
|

Plasma sterol evidence for decreased absorption and increased synthesis of cholesterol in insulin resistance and obesity

Abstract: Cholesterol absorption was highest in the LIS participants, whereas cholesterol synthesis was highest in the LIR and OIR participants. Therapeutic diets for hyperlipidemia should emphasize low-cholesterol diets in LIS persons and weight loss to improve S(I) and to decrease cholesterol overproduction in LIR and OIR persons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 41 publications
2
25
2
1
Order By: Relevance
“…In contrast to the increased levels of cholesterol precursors, plant sterols such as sitosterol, campesterol, and stigmasterol, which partially reflect dietary sterol absorption, are decreased in obese subjects consuming controlled diets [7,9]. In this study, plant sterols tended to be slightly lower in overweight or obese children, in particular the levels of sitosterol and campesterol in obese boys were significantly lower (P < 0.001; Table 2).…”
Section: [ ( F I G _ 2 ) T D $ F I G ]contrasting
confidence: 55%
See 2 more Smart Citations
“…In contrast to the increased levels of cholesterol precursors, plant sterols such as sitosterol, campesterol, and stigmasterol, which partially reflect dietary sterol absorption, are decreased in obese subjects consuming controlled diets [7,9]. In this study, plant sterols tended to be slightly lower in overweight or obese children, in particular the levels of sitosterol and campesterol in obese boys were significantly lower (P < 0.001; Table 2).…”
Section: [ ( F I G _ 2 ) T D $ F I G ]contrasting
confidence: 55%
“…Serum lathosterol levels increase progressively with BMI [9], while weight loss is shown to reduce lathosterol levels [22]. In addition, visceral obesity and dyslipidaemic patients with greater visceral fat have significantly higher lathosterol levels and cholesterol synthesis [23,24].…”
Section: [ ( F I G _ 2 ) T D $ F I G ]mentioning
confidence: 99%
See 1 more Smart Citation
“…Of particular interest were associations for glycerol and lathosterol because prior studies had been small and replication was needed (Puhakainen et al , 1992;Paramsothy et al , 2011). Glycerol is a three-carbon molecule that forms the backbone of all triglycerides and blood levels of glycerol reflect the rate of fatty acid breakdown (Puhakainen et al , 1992;Venables et al , 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Excess exposure to insulin is commonly seen in overweight or obese subjects with insulin resistance and hyperinsulinemia. Increased levels of cholesterol synthesis and plasma cholesterol are also frequently seen in these same subjects (44). Numerous studies have shown an association of the increased cholesterol level with the development of various cardiovascular disorders, which are tightly connected to mitochondrion-derived oxidative stress (19,45).…”
Section: Discussionmentioning
confidence: 98%